IMPLEMENTASI MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN DI SMA NEGERI 1 PAMIJAHAN - Nugraha, Acep; Hartati, Siti Sri; Ridwansyah M, Jajang (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2024)
The management of educational facilities and infrastructure is one of the important elements that contribute to the advancement of education. The purpose of this study is to describe the implementation of facility and infrastructure management at SMAN 1 Pamijahan. The method applied is a qualitative descriptive approach, focusing on the facilities and infrastructure staff at SMAN 1 Pamijahan. Data were obtained through interviews, observations, and documentation. This study found that the management of facilities and infrastructure at SMAN 1 Pamijahan is carried out optimally and organized, covering all stages from initial planning, procurement process, routine maintenance, orderly storage, inventory recording, to the final disposal stage. This process aims to ensure that educational facilities and infrastructure are always in good, orderly, and well-maintained condition.